1999
DOI: 10.14712/18059694.2019.151
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Adhesion Molecules (sICAM-1, sVCAM-1, sE-selectin) and Neopterin in Patients with Sjögren's Syndrome

Abstract: Sjögren's syndrome is a systemic autoimmune disease characterized by focal lymphocytic infiltration of the salivary and lacrimal glands. Expression and up-regulation of adhesion molecules and activation of cellular immune system is essential for the migration of inflammatory cells into tissues. Soluble forms of adhesion molecules sICAM-1, sVCAM-1, sE-selectin and neopterin were analyzed in serum of 17 patients with primary Sjögren's syndrome and 11 patients with secondary Sjögren's syndrome together with 26 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Elevated levels of serum and/or urinary NP have been observed in rheumatoid arthritis (61, 62), glomerulonephritis (14, 63), Sjogren’s syndrome (64) and Grave’s disease (65). In autoimmune diseases, NP is produced locally by the infiltrating macrophages (8).…”
Section: Neopterin and Autoimmune Diseasesmentioning
confidence: 99%
“…Elevated levels of serum and/or urinary NP have been observed in rheumatoid arthritis (61, 62), glomerulonephritis (14, 63), Sjogren’s syndrome (64) and Grave’s disease (65). In autoimmune diseases, NP is produced locally by the infiltrating macrophages (8).…”
Section: Neopterin and Autoimmune Diseasesmentioning
confidence: 99%
“…Interestingly, immunoblotting showed that the cell surface receptor for advanced glycation end products (RAGE) was overexpressed in labial salivary glands of SS patients relative to control samples, with the opposite pattern observed in serum . In addition, serum levels of the soluble (s) forms of highly glycosylated adhesion molecules, sICAM-1, sE-selectin, neopterin, and sL-selectin, were significantly elevated in SS patients as compared with a control group. , Recently, it was reported that the concentration of MUC5B and MUC7 in whole saliva were similar between pSS patients and healthy individuals. Nevertheless, immunoblotting and glycan staining revealed a pSS-associated reduction in mucin glycosylation that was particularly prominent in association with MUC7 …”
Section: Introductionmentioning
confidence: 99%
“…Thirty studies (34 study groups) reported serum or plasma neopterin concentrations in a total of 2,618 RD patients (mean age 43 years, 32% males) and 5,318 healthy controls (mean age 42 years, 47% males) ( 55 , 59 , 61 , 64 67 , 69 – 87 , 89 , 90 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies were conducted in Asia ( 55 , 59 , 65 , 66 , 69 , 70 , 72 74 , 77 , 78 , 80 82 , 84 89 ), six in Europe ( 61 , 62 , 64 , 67 , 79 , 90 ), three in Africa ( 71 , 75 , 83 ), and the remaining one in America ( 76 ). Ten study groups included patients with RA ( 55 , 76 , 78 81 , 83 , 86 , 89 , 90 ), nine with SLE ( 55 , 65 , 70 , 71 , 75 77 , 82 , 84 ), eight with BD ( 59 , 65 , 66 , 69 , 72 74 , 87 ), three with IIM ( 62 , 88 ), two with pSS ( 64 , 67 ), one with SSc ( 61 ), and one with AS ( 85 ). The analytical methods used for measuring neopterin included an enzyme-linked immunosorbent assay (ELISA) in 18 studies ( 61 , 64 67 , 69 – 71 , 74 76 , 78 , 79 , 81 , 85 , 86 ,...…”
Section: Resultsmentioning
confidence: 99%